2014
DOI: 10.1128/aem.03434-13
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Robustness of Lactococcus lactis Strains during Heat Stress, Oxidative Stress, and Spray Drying Stress

Abstract: f In this study we tested 39 Lactococcus lactis strains isolated from diverse habitats for their robustness under heat and oxidative stress, demonstrating high diversity in survival (up to 4 log units). Strains with an L. lactis subsp. lactis phenotype generally displayed more-robust phenotypes than strains with an L. lactis subsp. cremoris phenotype, whereas the habitat from which the strains had been isolated did not appear to influence stress survival. Comparison of the stress survival phenotypes with alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 41 publications
4
43
0
Order By: Relevance
“…Instead, the transcriptional responses of L. lactis KF147 in ATL were similar to the downregulation of general stress response genes found during glucose starvation (38). Notably, the locus llkf_1440 to -1446, which contained the most highly induced gene in our study (llkf_1445), was previously negatively correlated with tolerance against heat stress (36). However, those genes are annotated to have roles in sugar metabolism, and their specific functions in thermal sensitivity have yet to be determined.…”
Section: Discussionsupporting
confidence: 67%
“…Instead, the transcriptional responses of L. lactis KF147 in ATL were similar to the downregulation of general stress response genes found during glucose starvation (38). Notably, the locus llkf_1440 to -1446, which contained the most highly induced gene in our study (llkf_1445), was previously negatively correlated with tolerance against heat stress (36). However, those genes are annotated to have roles in sugar metabolism, and their specific functions in thermal sensitivity have yet to be determined.…”
Section: Discussionsupporting
confidence: 67%
“…This relationship could be attributed to OTC inducing the increase of and OTC-treated fish were detected. In this way, bands related to Lactobacillus genus were only detected in fish treated with OTC+SpPdp11, and it has been reported that different species of Lactobacillus show the ability to produce antioxidant molecules and reduce oxidative stress [72,73].…”
Section: Discussionmentioning
confidence: 86%
“…lactis or intestinal robustness phenotype variations among strains of Lb. plantarum did identify genes with correlated gene presence-absence patterns, subsequent mutational analyses did not verify their function in the respective phenotypes (631,632).…”
Section: Gene Function Discovery By Phenotype Diversity Mining Stratementioning
confidence: 99%